Effects of Asbestos Exposure and Health Belief Model on Health Preventive Behaviors and Health Status among Car-Repair Workers - Saisut, Suphawan; Silapasuwan, Pimpan; Viwatwongkasem, Chukiat; Suwanaumpai, Plernpit (Journal of Health Science of Thailand, 2017)
Asbestos is a carcinogen even in small doses. Appropriate preventive behavior could reduce the risk of diseases. This analytical descriptive research was on asbestos exposure, and how Health Belief Model affects health preventive behaviors for asbestos exposure and the health status among car-repair workers in Ratchaburi province, Thailand. Data collection was conducted by analyzing brake dust; forty two samples of automobile brake dust from each of 14 garages, where 128 mechanics worked, were collected and examined by X-ray diffractometer to determine the presence of asbestos fibers. Data were also gathered using interview forms, which were divided into 4 parts: general characteristics; Health Belief Model; health preventive behaviors for asbestos exposure and health status. The result showed that 15 brake dust samples (35.7%) contained Chrysotile asbestos. Most of the study subjects (71.1%) had preventive behaviors for asbestos exposure at a low level and 14.8 percent of the workers had symptoms of respiratory distress, such as coughing. In addition, the results of the stepwise regression analysis revealed that perceived benefits and obstacles to preventa asbestos exposure, health motivation, tobacco smoking, work hours and asbestos examination significantly affected preventive behaviors for asbestos exposure. The findings suggested that in order to encourage preventive behaviors for asbestos exposure among car-repair workers, health promotion programs focusing on providing information about the hazard of asbestos exposure, reinforcing of health motivations, reducing obstacles, increasing perceived benefits and reducing tobacco smoking are recommended.